2006
DOI: 10.1111/j.1365-2516.2006.01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of validity of clinical, X‐ray and magnetic resonance imaging scores in evaluation and management of haemophilic arthropathy in children

Abstract: To evaluate joints alterations, we performed clinical examination, X-rays and magnetic resonance imaging (MRI) (Denver score) in 165 joints of 40 children with severe (n, 32) or moderate (n, 8) haemophilia A or B. All investigated joints had a history of more than three bleeds. At evaluation, 25 of 40 haemophilic patients were on prophylaxis for the last 1-8 years (mean: 3.5 years). MRI revealed chronic synovitis in 55.4% and 50% of joints, which were diagnosed, as normal by the clinical scale and plain radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 22 publications
4
96
0
1
Order By: Relevance
“…1 Recurrent hemarthroses result in progressive joint damage and the development of painful and debilitating hemophilic arthropathy. 2 Replacement therapy with FIX products, manufactured from plasma (pdFIX) or more recently by recombinant technology (rFIX), is presently used to control and prevent bleeding episodes. 3,4 Prophylaxis is currently considered optimal care for patients with severe hemophilia 5 because it reduces the incidence of all bleeding episodes and, when initiated at a very young age, also reduces the risk of arthropathy development.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recurrent hemarthroses result in progressive joint damage and the development of painful and debilitating hemophilic arthropathy. 2 Replacement therapy with FIX products, manufactured from plasma (pdFIX) or more recently by recombinant technology (rFIX), is presently used to control and prevent bleeding episodes. 3,4 Prophylaxis is currently considered optimal care for patients with severe hemophilia 5 because it reduces the incidence of all bleeding episodes and, when initiated at a very young age, also reduces the risk of arthropathy development.…”
Section: Introductionmentioning
confidence: 99%
“…Second, joint destruction from inflammation due to recurrent articular haemorrhage. The latter mechanism appears similar to the changes seen in haemophilic arthropathy, with synovial thickening and haemosiderin deposits initiating the inflammatory changes leading to arthropathy [10,11].…”
Section: Discussionmentioning
confidence: 83%
“…We checked mean levels of FVII before and after administration of the 2 rFVIIa preparations to prove FVII: C level was comparably increased. 6,38 In the previous studies, the rate of reported adverse events was 1% to 10%, [50][51][52][53][54][55][56][57][58][59][60] and the most of adverse events had been headache, rashes, hypertension, and rarely thrombosis. We did not encounter any thrombosis in either treatment groups.…”
Section: Discussionmentioning
confidence: 98%